Tradução para o português (Brasil), adaptação transcultural e avaliação da reprodutibilidade da Escala de Bristol para Consistência de Fezes modificada para crianças - Jozala, Debora Rodrigues [UNESP]; Oliveira, Isabelle Stefan de Faria [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; de Oliveira Junior, Wilson Elias [UNESP]; Comes, Giovana Tuccille [UNESP]; Cassettari, Vanessa Mello Granado [UNESP]; Self, Mariella Marie; Lourenção, Pedro Luiz Toledo de Arruda [UNESP] (Elsevier, 2018)
Objective: To translate and culturally adapt the modified Bristol Stool Form Scale for children into Brazilian Portuguese, and to evaluate the reproducibility of the translated version. Methods: The stage of translation and cross-cultural adaptation was performed according to an internationally accepted methodology, including the translation, back-translation, and pretest application of the translated version to a sample of 74 children to evaluate the degree of understanding. The reproducibility of the translated scale was assessed by applying the final version of Brazilian Portuguese modified Bristol Stool Form Scale for children to a sample of 64 children and 25 healthcare professionals, who were asked to correlate a randomly selected description from the translated scale with the corresponding representative illustration of the stool type. Results: The final version of Brazilian Portuguese modified Bristol Stool Form Scale for children were evidently reproducible, since almost complete agreement (k > 0,8) was obtained among the translated descriptions and illustrations of the stool types, both among the children and the group of specialists. The Brazilian Portuguese modified Bristol Stool Form Scale for children was shown to be reliable in providing very similar results for the same respondents at different times and for different examiners. Conclusion: The Brazilian Portuguese modified Bristol Stool Form Scale for children is reproducible; it can be applied in clinical practice and in scientific research in Brazil.
Brazilian Portuguese translation, cross-cultural adaptation and reproducibility assessment of the modified Bristol Stool Form Scale for children
Keywords: Child; Constipation; Defecation; Reproducibility of results; Translations